One or Two Stages Procedure for Repair of Rectovestibular Fistula: Which is Safer? (A Single Institution Experience) - Mohammed Khalifa; Khalid Shreef; Mohammad Ahmad Al Ekrashy; Tarek Abdelazim Gobran (Wolters Kluwer Medknow Publications, 2017)
Background: Rectovestibular fistula (RVF) is the most common type of anorectal malformations in females. The need for a diverting colostomy during correction of defect has ignited a heated debate. In this study, we reviewed the girls with RVF that had been treated by either one or two stage procedure in the past 10 years in our institution to define whether one stage or two stage procedures is safer and more beneficial for the patients. Materials and Methods: Seventy girls with RVF that had been operated from January 2005 to January 2015 were studied retrospectively. Data were obtained from medical hospital records. The cases were divided into two groups. Group A (46 patients): were operated by two stages technique (simultaneous sigmoid colostomy and anterior sagittal anorectoplasty [ASARP]). Group B (24 patients): were operated by one stage (ASARP without covering colostomy). The short-term outcome as regard wound infection, wound dehiscence, anal stenosis, anal retraction, recurrence of fistula as well as complications of colostomy was reported. The long-term outcome as regard soiling, constipation and voluntary bowel movement was evaluated. Results: The age of patients at the time of surgery ranged from 3 months to 2 years (mean; 9.5 months). In Group A, seven patients (15.2%) developed wound infection, two patients developed wound disruption. One patient developed anterior anal retraction and required redo-operation, anal stenosis was noticed in five (10.9%) patients. Complications from colostomy had occurred in nine patients (19.5%). In Group B, wound infection occurred in ten patients (41.7%). Seven patients (29.2%) developed wound disruption. Anal stenosis occurred in eight patients (33.3%). Five patients required redo-operation because of anal retraction in three patients and recurrence of fistula in the other two patients. Constipation recorded in 15 patients (32.6%) of Group A and in ten patients (41.3%) of Group B. Soiling was reported in six girls (13.04%) of Group A and five girls (20.8%) of Group B. Conclusion: The avoidance of colostomy is not outweighed achieving sound operation and continent child. Two stages correction of RVF is safer and more beneficial than one stage procedure, especially in our locality and for our paediatric surgeons during their learning curve.